The Effect Of Compound Exercises Using Visual Training Aid On Tactical Performance Of Deaf Soccer League Players - Talib, Nawras; Ali, Suha (Journal of Physical Education, 2019)
All Sports, especially football, has witnessed a remarkable development in recent times as part of scientific development of sports achievements. Deaf football is one of the most important team sports in the world and its players must be fully aware of the developments that are taking place. Since tactical performance is the most important element of the game,  the researchers aimed at finding a suitable way for developing tactical performance by designing a set of special compound exercises using visual aid due to its great role in developing tactical performance and scoring during competitions.